Elements of intertextuality in some selected poems of the Diwan of Sultan Muhammad Bello of Nigeria - Kaoje, Abubakar Usman; Toklubok, Pabiyah; Syed Abdullah, Syed Nurulakla (Human Resource Management Academic Research Society (HRMARS), 2024)
Intertextuality is a term that indicates that all texts whether written or spoken, formal or informal, artistic or mundane, are in some ways related to one another. The relationship might be historical, psychoanalytical, Marxist, etc. Intertextuality as a form of literary theory has been specifically chosen in this study to interpret and analyse the phenomena of intertextuality in Sultan Muhammad Bello's artistic works, particularly poems. The theory's selection is noteworthy considering its importance among critics and literary scholars. The study attempts to explain how the literary theory of intertextuality can be used to analyse or interpret the literary works of Sultan Bello. The study establishes the availability of various forms of intertextuality (religious, literary etc, in his works). Finally, the selection of Sultan Bello's works for this academic activity is heavily influenced by his great contribution to the field of education and knowledge as a whole. Given the above, the research has the following questions to answer: What are the elements of intertextuality found in the Diwan of Sultan Muhammad Bello? Are there elements of religious and literary forms of intertextuality in his Diwan.